Ekonomi Politik Media; Historis hingga Praksis - Tommy Satriadi Nur Arifin (AKADEMI KOMUNIKASI RADYA BINATAMA, 2021)
AbstractThis paper discusses the study of the political economy of the media in terms of historical aspects to current conditions. Political economy is not a study that was born from the merger of the two phrases “economics” and “politics”, but rather as a new andwhole concept with ideological assumptions. Political economy also significantly influences the existence of mass media entities, both scientifically and in implementation, so that it is better known as media political economy. Following its development, the political economy of the media has become a separate study, especially media studies and communication studies. Media content is determined by economic and political forces outside the media. Media owner factors, capital, advertising, government regulations determine the content of the media.Keywords: Economy, Politics, Media, Political Economy of Media, History